Customer satisfaction towards facilities and services provided at food court in shopping complex / Noorshiela Mat Amin - Mat Amin, Noorshiela (Faculty of Architecture, Planning and Surveying, 2013)
Food court management is a part of the facilities management. The management of the food court is similar to the facilities management. The principle of facilities management is the combination of work process, people and place. In meanwhile, management at food court used the principle in perform a good management to the food court. The management will ensure the process of work will fulfil the customer satisfaction. The management monitor the work process at the kitchen and preparation of foods. They integrate with worker and customer to enhance the managing performance. This management will covered the whole food court in term of inspection, maintaining the facilities and services at the food court. Facilities management in mall is an integrated approach in maintaining, improving and adapting the buildings in order to create a good environment and it ill support the business in the mall itself. The rapid economic growth will change the behaviour of customer. The satisfaction of customer is the master mind in the changing of economic growth. The satisfaction can be measured to determine the level of satisfaction towards the performance of the management is effective and relevant to fulfil the customer satisfaction. As customer satisfaction change the level of performance, customer is more important in this situation in order to give a good of facilities services and a quality of services. The measurement of customer satisfaction should be evaluate and determine by the food court management to improve performance of the management. The satisfaction level should be measured on selling price of a meal, air circulation at food court is important to bring a comfort level, satisfaction on the lighting, air conditioning, cleanliness and hygiene and other facilities and services provided to fulfil the customer needs, expectation, perception and satisfaction.